Vai trò của kế toán trong thúc đẩy quá trình chuyển đổi số của doanh nghiệp sản xuất tại Việt Nam: Nghiên cứu định tính - Nguyễn Thị Than, Trầm; Phạm Ngọc , Toàn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
While most existing studies focus on examining the impact of digital transformation on accounting functions, the agentic role of accountants in shaping digital transformation at the organizational level remains underexplored. This study adopts a qualitative research approach based on nine in-depth interviews with production directors, chief financial officers, chief information officers, chief accountants, and accounting staff from manufacturing firms. Data were analyzed using Braun and Clarke’s (2006) six-phase thematic analysis, with data management and coding supported by the Taguette software. The findings reveal four main themes: (1) drivers of digital transformation; (2) shaping digital culture and managing change; (3) accounting data as a foundation for digital transformation; and (4) accounting competencies and mindset. However, the role of accountants in digital transformation is found to be conditional, depending on organizational decision-making structures, the level of system integration, and the firm’s strategic orientation. These findings provide new insights into the roles and mechanisms through which accountants contribute to digital transformation, while also offering implications for policymakers and business managers.